Strategic initiatives to increase the player base in Portuguese women´s football: recruiting more - Hagelberg, Marieke Jörna (2022)
The present project derives from the Portuguese Football Federation’s 2015-2020 Women’s Football Strategic Plan, with the purpose of evaluating and evolving its outcomes, specifically concerning the first strategic objective: broadening the player base in Portugal. Against the background of this objective, it focuses on the challenge of recruiting more players. To address this challenge, the project leverages on sports management literature to analyse the internal and external context, while benchmarking other football associations’ successful initiatives, culminating on a set of recommendations to achieve the strategic evolvement in coordination with the Portuguese Federation’s priorities and objectives.